2016
DOI: 10.1002/2016gc006460
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of seismic coupling on normal fault style along the Northern Mid‐Atlantic Ridge

Abstract: Key points• Greater seismic moment release rates at detachment-bearing sections of the Mid-Atlantic Ridge compared to abyssal hill-bearing sections.• Coupled seismic thickness likely greatest (~2 km) at individual detachment faults of finite along-axis extent, and averages ~500 m elsewhere.• Rate and state friction theory attributes differences in seismic coupling to the thermomechanical state and lithology of oceanic normal faults. AbstractWhile normal faults are essential in shaping the seafloor formed at sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 99 publications
(233 reference statements)
1
21
1
Order By: Relevance
“…Cowie et al () found the coupling coefficient for faults bounding the fast‐spreading East Pacific Rise to be less than 0.01. By contrast, estimates derived using teleseismic and hydroacoustic data from the slow‐spreading Mid‐Atlantic Ridge indicate coupling coefficients of 0.1–0.3 for symmetric ridge segments and 0.4–0.6 for segments characterized by the presence of large‐offset detachment faults (Olive & Escartín, ). Frohlich and Wetzel () found a similar systematic variation in the coupling coefficient across a range of spreading rates using teleseismic moment release rates.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Cowie et al () found the coupling coefficient for faults bounding the fast‐spreading East Pacific Rise to be less than 0.01. By contrast, estimates derived using teleseismic and hydroacoustic data from the slow‐spreading Mid‐Atlantic Ridge indicate coupling coefficients of 0.1–0.3 for symmetric ridge segments and 0.4–0.6 for segments characterized by the presence of large‐offset detachment faults (Olive & Escartín, ). Frohlich and Wetzel () found a similar systematic variation in the coupling coefficient across a range of spreading rates using teleseismic moment release rates.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have also addressed seismic behavior and the potential for aseismic slip on faults at divergent plate boundaries (e.g., Biemiller & Lavier, ; Calais et al, ; Cowie et al, ; Olive & Escartín, ; Sobolev & Rundquist, ). Observations support a range of behavior from seismic and aseismic fault slip across different ridges and ridge segments (Cowie et al, ; Olive & Escartín, ). However, interpretation of these variations has been limited due to the lack of quantitative models for seismic cycles on mid‐ocean ridge normal faults.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations